Tantangan dan Peluang Pendidikan Islam di Era Global Village - Nurul Ashiqin; Rafika Hasanah; Reina Aulia Revi; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Education as a role holder in the development process both institutionally, educational materials, teachers as implementers of learning, methods, facilities, and so on from all aspects and supporting factors of the educational process, must be able to look carefully and be able to build a new paradigm in the form of education in the global era which is full of challenges, so that it can provide new space for several opportunities that can provide new perspectives and contribute to the development of the global world. Research on Challenges and Opportunities for Islamic Education in the Global Village Era aims to identify challenges and opportunities for Islamic education in the global world and provide solutions to improve understanding and appreciation of Islam. Research on Challenges and Opportunities for Islamic Education in the Global Village Era can be carried out using a qualitative approach with research methods. bibliography and descriptive. In its development, the global village has had positive and negative impacts on human life. The impact it creates is in line with the process of transforming information that can be accessed more quickly in various parts of the world as the globalization of the world has changed the pattern of life in various aspects and sides. The phenomenon that was awakened by the emergence of the global village era has provided various kinds of problems, both about how information that continues to grow indiscriminately can be absorbed or how to respond to new things that always come and go without any filters to filter them. The era of the global village with its development of information technology can increasingly be felt, with the media in the form of computers, televisions, cellphones and other sophisticated equipment, which have truly become complex things in the transformation of information.